2021
DOI: 10.1177/09504222211053262
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between entrepreneurship education, motivations, and intention among Indian university students: The role of psychological and contextual factors

Abstract: This study assesses the impact of different psychological and contextual factors on entrepreneurial motivations and the role of entrepreneurial motivations in determining the entrepreneurial intention of students at Indian universities. The paper also explores whether gender acts as a moderator in the entrepreneurial motivation–intention relationship. Cross-sectional data were collected by administering a questionnaire to 329 students who had received entrepreneurship education during their course program. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 138 publications
2
29
0
3
Order By: Relevance
“…Several researchers examined contextual factors as direct predictors of entrepreneurial intentions. For example, Hassan et al (2021) found that government policy support and financial access as contextual factors did not affect the students’ motivation to become entrepreneurs. Tran Anh and Von Korflesch (2016) designed a contextual factors model as a predictor to cultivate entrepreneurial intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers examined contextual factors as direct predictors of entrepreneurial intentions. For example, Hassan et al (2021) found that government policy support and financial access as contextual factors did not affect the students’ motivation to become entrepreneurs. Tran Anh and Von Korflesch (2016) designed a contextual factors model as a predictor to cultivate entrepreneurial intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The most important contribution that cognitive science offers to the entrepreneurship research is that we apprehend reality not directly, but through multiple perceptual lenses at different levels of interventionindividual, context and environment and society (Grégoire et al, 2011;Rantanen and Toikko, 2017;Dileo and García Pereiro, 2019). Empirical evidence indicates that launching a successful venture requires a potential entrepreneur to have the necessary entrepreneurial skills, knowledge and experiences (Kedmenec et al, 2014;Elnadi and Gheith, 2021;; a role model and motivation from successful entrepreneurs (Cinar et al, 2018;Choukir et al, 2019;Nowi nski et al, 2019;Amofah and Saladrigues, 2022); and less fear of failure (Cacciotti et al, 2016;Hassan et al, 2021;Sendra-Pons et al, Besides cognitive perceptions, it is important to consider the perceptions of economic opportunities, which can also be influencing entrepreneurial intention (Yasir et al, 2017;Dubey and Sahu, 2022;Kong and Kim, 2022). The growing viability of entrepreneurship from an economic standpoint, and as an individual career option, has recently generated a vast amount of research (Barnir et al, 2011).…”
Section: Cognitive Economic and Social Factors And Entrepreneurial In...mentioning
confidence: 99%
“…About one-third of entrepreneurs in the world belong to the need-based category, in which new start-ups are launched mainly due to the absence of other opportunities (Reynolds et al, 2002). The rest two-thirds of the entrepreneurs belong to the motivation-based category in which opportunities and motivation play more prominent roles (Hassan et al, 2021; Reynolds et al, 2002). On one hand, India is an emerging and rapidly growing economy.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%